Application of Smartphone Otoscope in Telemedicine in Rural Medical Consortium in Eastern China in the COVID-19 Era - Meng, Xiangming; Dai, Zhiyong; Wang, Ying; Hua, Xiang; Gu, Xiaobo; Guo, Jianxun; Wang, Yangyang; Hang, Chao; Jiang, Yuting (Frontiers in Public Health, 2022)
Purpose: This study aimed to evaluate the effectiveness of smartphone otoscope telemedicine in the rural medical consortium in East China in the COVID-19 era. Methods: This prospective study was conducted within a rural medical consortium that provides health care services by integrating medical resources in the same area. When a patient visited primary health care (PHC) for ear diseases, the PHC provider used a smartphone otoscope to examine the patient's external ear canal and eardrum, and then sent photos or videos of the patient's ear to the otolaryngologist at the lead hospital via WeChat group. The otolaryngologist provided remote diagnosis and management recommendations to the PHC provider. The following data were recorded: age and gender, outpatient diagnosis, disease duration, sides, duration of treatment, telemedicine visits, treatment outcomes, patient satisfaction, and PHC providers' self-evaluation score. Results: A total of 83 patients were included in the study, including 43 males and 40 females, with a mean age of 44.6 ± 19.7 years (range 3–83 years). The duration of treatment for these patients was14.0 (7,14) days. PHC visits were 2.2 ± 1.1 times (range: 1-7 times). Telemedicine visits ranged from 1 to 5, with a mean of 1.8 ± 0.9. Among of patients, 62 (74.7%) were cured, 21 (25.3%) improved, and 0 (0%) were ineffective. Sixty-five patients (78.3%) were very satisfied, 16 (19.3%) patients were somewhat satisfied, and 2 patients (2.4%) were dissatisfied. Based on the self-reported helpfulness, the primary health care providers assessed telemedicine as very helpful (n=63, 75.9%), helpful (n=20, 24.1%), and unhelpful (n=0, 0%). Conclusions: Smartphone otoscope telemedicine in the medical consortium can effectively improve the ability of rural PHC providers to diagnose and treat ear diseases, save time and costs for patients, and improve patient satisfaction.